PLYOMETRIC EXERCISES WITH HIGH AND LOW INTENSITIES HAVE AN IMPACT ON ATHLETES’ MAXIMUM VOLUNTARY ISOMETRIC CONTRACTION AND VERTICAL JUMP HEIGHT. - BP, SATHISH; RAJAN, Dr. A. KALEB; M.G., Dr. MUNIRAJU (The journal of contemporary issues in business and government, 2023)
The study involved 24 athletes with ages ranging from 20 to 30. The individuals were randomized into two groups, high and low intensity plyometric groups, at random. Exercises including double and single leg vertical leaps, single leg tuck jumps, and other high-intensity plyometric exercises were provided to the high-intensity plyometric group. Split and cycled squat jumps were given to the low-intensity plyometric group. During four weeks, both groups received plyometric training. The maximal voluntary isometric contraction and vertical leap were measured in both groups at the beginning, the second, and the fourth weeks of training. After 4 weeks, high-intensity and low-intensity plyometric workouts in the current research improved vertical jump height and maximum voluntary isometric contraction to varying degrees.